The importance of long-term financing by banks: Advantages and future challenges - Michael Hüther; Michael Voigtländer; Heide Haas; Philipp Deschermeier (Institut der deutschen Wirtschaft (IW), 2015)
Long-term financing plays an important part in calming the markets and thus ensuring the stability of economies. The German market for residential real estate financing provides an impressive example of this. However, new financial market regulations such as Basel III and Solvency II will cause the market for long-term financing to contract, as banks will be incentivised to grant more short-term loans. Other financial intermediaries such as insurance companies or funds are unlikely to be able to close this gap. Although alternative financial intermediaries will increase their lending due to advantages in regulation, they will be unable to eliminate the shortage of long-term financing, owing to a lack of experience and incentives. The regulatory framework must therefore be adapted to make the banking sector more robust while simultaneously allowing it to continue to fulfil its original economic functions. – – Langfristige Finanzierungen tragen wesentlich zur Beruhigung der Märkte und damit zur Stabilität von Volkswirtschaften bei. Dies zeigt eindrucksvoll das Beispiel des deutschen Marktes für Wohnungsfinanzierungen. Bedingt durch die neuen Finanzmarktregulierungen wie Basel III und Solvency II wird sich der Markt für langfristige Finanzierungen jedoch verkleinern, da Banken Anreize erhalten, eher kurzfristige Darlehen zu vergeben. Andere Finanzintermediäre, etwa Versicherungen oder Fonds, werden diese Lücke kaum schließen können. Zwar werden alternative Finanzintermediäre aufgrund von Vorteilen in der Regulierung ihre Kreditvergabe erhöhen, aber wegen fehlender Erfahrungen und Anreize werden sie den Mangel an Langfristfinanzierungen nicht beheben können. Geboten ist daher eine Anpassung des Regelwerks, damit der Bankensektor robuster wird, gleichzeitig aber seine originären volkswirtschaftlichen Funktionen weiter erfüllen kann.
urn:nbn:de:101:1-201503232995
Keywords: 330; Fremdkapital; Fälligkeit; Immobilienfinanzierung; Kreditgeschäft; Basler Akkord; Deutschland